2005
DOI: 10.1111/j.0906-7590.2005.04001.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the “safe nesting zone” hypothesis across an urban gradient: a multi‐scale study

Abstract: . Evaluation of the ''safe nesting zone'' hypothesis across an urban gradient: a multi-scale study. Á/ Ecography 28: 59 Á/70.Urban areas have been considered ''safe zones'' for nesting birds because of low abundance of predators, and consequently low predation pressure. We studied risk of artificial ground nest predation across an urban gradient at regional (100)/100 km) and local scales (5)/5 km, within town) in Finland, Italy, and Spain. Risk of nest predation differed between countries, being greatest in Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
3
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 57 publications
3
56
3
2
Order By: Relevance
“…Blair, 1996;Bolger et al, 1997;Clergeau et al, 1998Clergeau et al, , 2006aJokimäki et al, 2005), whereas others have highlighted that local features (such as the reciprocal distribution of green areas or the vegetation diversity hosted by a given green area) may also influence bird communities and are of particular importance in estimating the likelihood of finding bird species (Clergeau et al, 2001;Melles et al, 2003). Our results showed that features at both landscape and local scales can explain bird community structures.…”
Section: Appendix a 1138mentioning
confidence: 55%
See 1 more Smart Citation
“…Blair, 1996;Bolger et al, 1997;Clergeau et al, 1998Clergeau et al, , 2006aJokimäki et al, 2005), whereas others have highlighted that local features (such as the reciprocal distribution of green areas or the vegetation diversity hosted by a given green area) may also influence bird communities and are of particular importance in estimating the likelihood of finding bird species (Clergeau et al, 2001;Melles et al, 2003). Our results showed that features at both landscape and local scales can explain bird community structures.…”
Section: Appendix a 1138mentioning
confidence: 55%
“…Urbanization acts against high canopy and foliage exploiters and strongly favours ground feeding-granivorous and omnivorous species vs. aerial insectivores (decreasing due to the urban pollution). Likewise it favours cavity nesting species (especially those using anthropogenic cavities) vs. "ground nesters" (Lancaster and Rees, 1979;Beissinger and Osborne, 1982;Mills et al, 1989;Allen and O'Conner, 2000;Jokimäki et al, 2005;Chace and Walsh, 2006;Clergeau et al, 2006a). According to our analysis of nesting functional groups, the increased urbanization level clearly represents a detriment for the species nesting on the ground, this being likely due to nest predation and decreasing habitat quality and availability (Jokimäki et al, 2005).…”
Section: Functional Groupsmentioning
confidence: 81%
“…Those observations indicate that the level of nest predation experienced by this species may depend on geographical location and may also be modified by the type of environment in which the birds nest (e.g., Thorington and Bowman 2003;Jokimäki et al 2005). This is because this species colonizes a variety of very different habitats (Mendelssohn and Yom-Tov 1999;Aghanajafizadeh et al 2011;Fröhlich and Ciach 2013).…”
Section: Reproductive Successmentioning
confidence: 99%
“…Such changes in predator communities are frequently cited as causes of the commonly reported negative association between some sensitive Neotropical migratory species and urbanization, yet the link between urbanization and increased nest predation has surprisingly mixed empirical support from studies of natural nests (Phillips et al 2005; Bakermans and Rodewald 2006; Burhans and Thompson 2006;Rodewald and Shustack 2008b). Most studies reporting higher rates of predation in urban environments have used artificial nests (Gering and Blair 1999;Jokimaki and Huhta 2000;Thorington and Bowman 2003;Jokimaki et al 2005), which can result in biased estimates of nest predation due to species-specific responses of nest predators (Thompson and Burhans 2004). Our long-term studies of nest predation in central Ohio and western Washington suggest that nest predation in urbanizing landscapes show high temporal and spatial variability, and urbanization seems to be inconsistently related to daily mortality rates (Marzluff et al 2007; A.D. Rodewald, unpublished data).…”
Section: Alteration Of Resources and Processes In Urbanizing Landscapesmentioning
confidence: 99%